Brain maturation is delayed in infants with complex congenital heart defects - Licht, Daniel J. (2009)
OBJECTIVE: Small head circumferences and white matter injury in the form of periventricular leukomalacia have been observed in populations of infants with severe forms of congenital heart defects. This study tests the hypothesis that congenital heart defects delay in utero structural brain development. METHODS: Full-term infants with hypoplastic left heart syndrome or transposition of the great arteries were prospectively evaluated with preoperative brain magnetic resonance imaging. Patients with independent risk factors for abnormal brain development (shock, end-organ injury, or intrauterine growth retardation) were excluded. Outcome measures included head circumferences and the total maturation score on magnetic resonance imaging. Total maturation score is a previously validated semiquantitative anatomic scoring system used to assess whole brain maturity. The total maturation score evaluates 4 parameters of maturity: (1) myelination, (2) cortical infolding, (3) involution of glial cell migration bands, and (4) presence of germinal matrix tissue. RESULTS: The study cohort included 29 neonates with hypoplastic left heart syndrome and 13 neonates with transposition of the great arteries at a mean gestational age of 38.9 ± 1.1 weeks. Mean head circumference was 1 standard deviation below normal. The mean total maturation score for the cohort was 10.15 ± 0.94, significantly lower than reported normative data in infants without congenital heart defects, corresponding to a delay of 1 month in structural brain development. CONCLUSION: Before surgery, term infants with hypoplastic left heart syndrome and transposition of the great arteries have brains that are smaller and structurally less mature than expected. This delay in brain development may foster susceptibility to periventricular leukomalacia in the preoperative, intraoperative, and postoperative periods.